Kemampuan Pemecahan Masalah Matematika Siswa dengan Menggunakan Model Pembelajaran Problem Based Learning (PBL) dan Group Investigation (GI) - Nur islamiati (Yayasan Pembina Lembaga Pendidikan (YPLP) PGRI Kabupaten Sumbawa Barat - NTB - Indonesia, 2023)
This study aims to determine whether or not there is a difference in mathematical problem solving abilities between students who apply the Problem Based Learning (PBL) learning model and students who apply Group Investigation (GI) learning. This research is a true-experimental quantitative approach with a post-test only control group design. The population in this study were all class X SMA IT Ad-Dakwah. The sample in this study was class XA which was taught using the problem based learning (PBL) learning model and XB was taught using group investigation (GI). The number of research samples is 40 students. The instrument of this research was to use a final test sheet for problem solving abilities. Data collection techniques using tests. The data analysis technique uses one-way ANOVA analysis with prerequisite tests, namely the Normality Test and Homogeneity Test. Analysis using the SPSS application version 29.0 for Window. The research results obtained were that there was a significant difference in the problem solving abilities of students who studied using the Problem Based Learning (PBL) learning model with the problem solving abilities of students who learned using the Group Investigation (GI) learning model. Obtained a significance value lower than the significance level of 0.05 (5%) or 0.001 <0.05 and F count is greater than F table or 12, 661 > 4, 098. The average value of PBL students is 80.90 and students GI of 73.80.